Differences in acid-resistant battery examination results ziehl neelsen method and Rapid Molecular Test (TCM) at Sekayu regional hospital in 2023 - Alkaff, M Nabil; Ernia, Rima; Wulandari, Eva (Science Midwifery, 2024)
Pulmonary tuberculosis is the most deadly infectious disease in the world, besides this disease is caused by Mycobacterium tuberculosis (MTB). Ziehl Neelsen examination and TCM (Rapid Molecular Test) are the methods used to detect Mycobacterium tuberculosis. The aim of this study was to determine the results of acid-resistant bacteria in pulmonary tuberculosis examination between the Ziehl Neelsen and TCM methods at Sekayu Regional Hospital. This type of research is quantitative analytical with a cross sectional approach by looking at the positive or negative results of patients suspected of having tuberculosis. The research method used was Ziehl Neelsen and TCM sputum examination methods. The results of the research from the 9 samples examined were that 6 samples were negative and 3 samples were positive in the Ziehl Neelsen microscopic examination method, while in the Molecular Rapid Test examination, 3 positive results were found for MTB Detected very Low and 6 (Negative) MTB Not Detected. The conclusion of this study is that there is no difference between the two methods. It is recommended that the public carry out BCG (Bacille Calmette Guerin) vaccination and ensure that the house has good air ventilation.